De la restauration à la rétromania : Adorno, Reynolds et l’enjeu du passé dans l’évaluation du présent musical - Trottier, Dannick (MUSICultures, 2022)
This article provides a comparison between the philosopher Theodor W. Adorno and the music critic Simon Reynolds by means of two essays: Philosophie de la nouvelle musique (1962 [1949]) and Rétromania. Comment la culture pop recycle son passé pour s’inventer un futur (2012 [2011]). From their positions as music critics and their work reviewing the music of their time, these two authors adopted a conception of the art form that shares many similarities with how we seek to understand music today. It is in this context that past knowledge serves as a benchmark against which we may judge the music of today through the concepts of restoration and retromania. These concepts bring a historicist interpretation of music into play that relies on the fetishism of the measures used by musicians, specifically the between-wars European avant-garde with Adorno and the 2000s Anglo-American pop and rock with Reynolds. In this way, and without forgetting that what separates these two men, when it comes to their philosophies and their aesthetic positions, is anchored in a modernist posture where notions of originality, progress, and rebellion dominate. That is why the study stops with the critique of the two men while, at the same time, deepens the theories at the heart of their essays and the scope of their concept where the idea of a “return to” occurs.